State Land, Private Homes: Legal Implications of Public Apartment Ownership in Bandung - Azis, Siti Aminah Abdul; Kanzu, De Atika; Handoyo, Kartika Putri (Universitas Negeri Semarang, 2025)
The construction of flats is carried out to accommodate people who do not have large land. The land that is the location for the construction of flats currently has ownership rights, building use rights, and use rights. Law Number 20 of 2011 (Law on Flats) regulates, considering that land rights to build flats are limited, especially in facilitating low-income people. However, the construction of flats on land owned by the government or regions still has many obstacles, so it has not been implemented. This study uses a descriptive analytical methodology with a normative legal approach. Library research data is analyzed qualitatively normatively. Based on the results of the study, the government is tasked with utilizing state or regional land in the form of land to build public flats. There are various challenges in providing public flats, both owned and rented. The government plans to issue a Building Ownership Certificate (SKBG) for Flat Units to overcome the obstacles to the demand for public flats. The flats were built as a pilot project in the city of Bandung. Since the implementing regulations for the SKBG Sarusun have just been issued, it is currently impossible to prove ownership of the SKBG Sarusun for public flats on land owned by the government or local government. Therefore, implementing instructions must be issued immediately.